Helene Schjerfbeck - Schjerfbeck, Helene 1862-1946; Lewison, Jeremy 1955- (Royal Academy of Arts, 2019)
A new study examining the life and work of Helene Schjerfbeck, the Finnish painter who influenced Bacon, Freud and Auerbach. Published to accompany a major retrospective at the Royal Academy, running from 20 July to 27 October 2019, the first time her works have been seen in London since 1890. Though little known outside her native country, Helene Schjerfbeck (1862-1946) is one of Finland's best-loved artists. Her career, which stretched from the late 1870s to the end of the Second World War, encompassed both Impressionism and Modernism. This book records an exhibition that marks the first time her works have been seen in the UK since she exhibited in London herself in 1890. It presents the full range of her exceptional paintings and drawings, with 70 works in all genres, including portrait, landscape and still-life. Schjerfbeck's technique, her social and cultural context and her legacy are all examined in depth by the authors. Her influence on such artists as Francis Bacon, Lucian Freud and Frank Auerbach is considered, while a series of self-portraits reveals the artist from youth to old age. The book also explores the role of the masquerade in Schjerfbeck's work, and the impact of old-master paintings on her practice
Published on the occasion of the exhibition Helene Schjerfbeck, Royal Academy of Arts, London 20 July - 27 October 2019, Ateneum Art Museum, Finnish National Gallery, Helsinki, 15 November - 26 January 2020
Keywords: Schjerfbeck, Helene -- 1862-1946; Schjerfbeck, Helene / 1862-1946; Schjerfbeck, Helene / 1862-1946 / Exhibitions; Women painters / Finland / Biography; Ausstellungskatalog -- Royal Academy of Arts -- 20.07.2019-27.10.2019 -- London; Ausstellungskatalog -- Ateneumin Taidemuseo -- 15.11.2019-26.01.2020 -- Helsinki